Frontal plane QRS-T angle may be a predictor for post-coronary artery bypass graft surgery atrial fibrillation - Kuyumcu,Mevlüt Serdar (2020)
SUMMARY BACKGROUND: New-onset postoperative atrial fibrillation (POAF) is the most common arrhythmia following coronary artery bypass graft surgery (CABG) and is associated with prolonged hospitalization, stroke, and mortality. The frontal plane QRS-T [f(QRS-T)] angle, which is defined as the angle between the directions of ventricular depolarization (QRS-axis) and repolarization (T-axis), is a novel marker of ventricular repolarization heterogeneity. The f(QRS-T) angle is associated with adverse cardiac outcomes. In light of these findings, in this study, we aimed to investigate the potential relationship between the f(QRS-T) angle and POAF. METHODS: 180 patients who underwent CABG between August 2017 and September 2018 were included in the study retrospectively. Two groups were established as patients who preserved postoperative sinus rhythm (n=130) and those who developed POAF (n=50). The f(QRS-T) angle and all other data were compared between groups. RESULTS: The fF(QRS-T) angle (p<0.001), SYNTAX score (p=0.039), serum high-sensitivity CRP levels (p=0.026), mean age (p<0.001), electrocardiographic left ventricular hypertrophy rate (LVH) (p=0.019), and hypertension rate (p=0.007) were higher, and the mean left ventricular ejection fraction (LVEF) (p<0.001) was lower in the POAF group. Multivariable logistic regression analyses demonstrated that lower LVEF (p=0.004), LVH (p=0.041), and higher age (p=0.008) and f(QRS-T) angle (p<0.001) were independently associated with POAF. CONCLUSIONS: High f(QRS-T) angle level is closely associated with the development of POAF. The f(QRS-T) angle can be a potential indicator of POAF.